Trauma-Sensitive Mindfulness for War Refugees: Communication of Preliminary Findings - Laila Jeebodh-Desai; Veronica M. Dwarika (Trauma Care, 2022)
Mindfulness and meditation was explored with the view to support the use of trauma-sensitive mindfulness (TSM) in clinical practice with survivors of war refugees in the treatment of post-traumatic stress disorders. The following questions were explored: (1) How are mindfulness and meditation defined? (2) What are the practices and perceived value of mindfulness practices? (3) What are the evidence and non-evidence-based treatments for post-traumatic stress disorder (PTSD)? (4) What are the possibilities of using TSM to support war-traumatised refugees in the treatment of PTSD in a refugee camp setting? Findings that measured currently actioned interventions for war-traumatised refugees did not account for psychological support that could be implemented in a refugee camp setting on a once-off basis. In response to the gaps and limitations highlighted, the study suggests an adaptation of the TSM intervention and professional development of practitioners in the art of TSM therapy.